2022
DOI: 10.3390/land11071091
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Meandering River Morphodynamics Using Satellite Remote Sensing Data—An Application in the Lower Deduru Oya (River), Sri Lanka

Abstract: River meandering and anabranching have become major problems in many large rivers that carry significant amounts of sediment worldwide. The morphodynamics of these rivers are complex due to the temporal variation of flows. However, the availability of remote sensing data and geographic information systems (GISs) provides the opportunity to analyze the morphological changes in river systems both quantitatively and qualitatively. The present study investigated the temporal changes in the river morphology of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
(51 reference statements)
1
3
0
Order By: Relevance
“…The high curvature of rivers drives the meandering process by causing erosion in the outer bank and accretion in the inner bank. The river curvature values are comparable with the values obtained in a similar study done for Deduru Oya in Sri Lanka [15]. However, the maximum curvature of the selected segment of the Mahaweli River is higher than that of the Deduru Oya River.…”
Section: Variation Of River Curvaturesupporting
confidence: 87%
See 2 more Smart Citations
“…The high curvature of rivers drives the meandering process by causing erosion in the outer bank and accretion in the inner bank. The river curvature values are comparable with the values obtained in a similar study done for Deduru Oya in Sri Lanka [15]. However, the maximum curvature of the selected segment of the Mahaweli River is higher than that of the Deduru Oya River.…”
Section: Variation Of River Curvaturesupporting
confidence: 87%
“…The importance of remotely sensed satellite data are their free and global availability and considerably high resolution (about 30 m). Further, some of these data are available for more than 30 years (ex: Landsat satellite data is available since 1984) [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graph digitization programs are used either as (i) rulers for identifying the values of particular data points from a graph, or (ii) tools for extracting entire data traces to re-create the graph. Examples of the latter include ultraviolet polarimetric data [34], x-ray diffraction data [35], oscilloscope data [36], cardiotocography data [37], tide-gauge data [38], earthquake signals [39], meandering river morphodynamics diagrams [40], and absorption and fluorescence spectra [16,[41][42][43][44][45][46][47]. We examined each available freeware program listed in Table 1, concluded that WebPlotDigitizer fits our needs, and downloaded an off-line version.…”
Section: Graph Digitization Programsmentioning
confidence: 99%